STRATEGI TATA KELOLA ADMINISTRASI PADA PERGURUAN TINGGI BERBASIS ELECTRONIC RECORDS - Hardiansyah, Hardiansyah; Fahmi, Agus (Universitas Pendidikan Mandalika, 2018)
Governance administration referred to in this research is how institutions organize, manage, and store data/records relating to the implementation of the administrative activities of Higher Education institutions, starting from the leadership down to the student level. The corporate governance is an activity that needs to be done effectively and efficiently in order to support productivity college. So far, the administration at the College still done conventionally. This is evident from the number of files and archives college piled up in the room and a filing cabinet. Thus, to find back the document that has been stored in cabinets require considerable time, besides that it must dismantle all the documents that have been previously arranged. The research method uses a qualitative approach, Draft Action Research utilizes quantitative data with qualitative data such as method mix focused on applied technology. Based on the research results obtained by the collected records in IKIP Mataram records are divided into several groups. By performing data reduction, grouping the records contained in the IKIP Mataram look that good governance based administration of electronic records has been applied properly. There are nine groups of records obtained in this study in which each group of records managed by each institution and the IKIP Mataram. Use of Electronic Records in the administration and other administrative activities at the IKIP Mataram very effective. All data on their activities and archives stored neatly in the respective chambers, structured data classification, and search data is quite efficient.Use of Electronic Records that can be controlled systematically to records from the time of creation or receipt, processing, distribution, organization, storage, retrieval up to destruction. Application of Electronic Records in higher education is relevant to the development and advancement of Science and Technology today, the program is a major concern so as to form a permanent administrative governance, especially at the IKIP Mataram.Keywords: Strategy, Governance, Electronic Records